Understanding the motivation of purchase decision making of KPOP Seventeen’s merchandise in Weverse Shop - Alexandrina, Elke; Ramonita, Latifa; Anindita, Arnika (Jurnal Mantik, 2024)
In the midst of society and the economy gradually recovering after COVID-19, there is one group that seems to be continuing to strengthen: Korean Idol lovers. In Jakarta alone, the Blackpink concert which was held on March 11-12, 2023, was a huge success, including other K-Idol concerts. Fans not only chase the concert tickets, but also buy up all available merchandise. Gaon Music Chart data sales on the katadata page even record sales of K-Pop physical albums reaching 53.73 million albums in 2021. This is the first-time physical album sales have exceeded 50 million since 2011. Weverse Shop currently is the largest e-commerce intermediary business, selling K-Pop-themed merchandise through applications and websites, based in South Korea. This shop is the go-to place for fans who want to collect merchandise from K-Pop artists, especially those under Pledis Entertainment, one of which is “Seventeen”. The pattern of purchases by fans is so massive, that they are willing to pre-order because they want to be the first to have the merchandise. Several production errors and merchandise delivery problems that had occurred with Seventeen's merchandise did not reduce the number of buyers, instead they were still sold out.  The theory used in this study is the ERG Theory from Clayton Alderfer which states that motivation is based on three needs, namely Existence, Relatedness, and Growth